Metabolism and Cytotoxic Mechanisms of Nitroglycerin in Isolated Rat Hepatocytes: Nitroglycerin metabolism and toxicity - Hossein Niknahad,; Peter J. O’Brien, (Iranian Journal of Pharmaceutical Sciences, 2012)
It has been proposed that organic nitrates such as glyceryl trinitrate (GTN), used in the treatment of cardiovascular diseases, act by producing nitric oxide (NO). However, the biochemical pathway for NO formation from GTN is not well understood. In the present study, we showed that nitrate formation from GTN, by isolated rat hepatocytes, was inhibited about 50% when cellular glutathione was depleted and about 40% when cytochrome P-450 was inactivated by SKF525A. This suggests that GTN is metabolized and/or NO is formed by three pathways in rat hepatocytes: 1) denitrification of GTN by GSH/GSH transferase system; 2) reduction of GTN by reduced cytochrome P-450; and 3) GTN can directly react with protein thiol groups of cellular macromolecules (transnitrosation). At much higher concentrations, GTN was toxic towards hepatocytes (LC50= 2 mM for 2 h of incubation) and cytotoxicity was accompanied by GSH and ATP depletion. Depleting GSH and/or inactivating cytochrome P-450 beforehand markedly increased GTN cytotoxicity. The permeable thiol reductant dithioteritol unlike antioxidants was found to be an effective antidote, even if added to the cells an hour after GTN. The results suggest that GTN-induced cytotoxicity is mediated by transnitrosyllation of mitochondrial, structural and vital protein thiols.